PELAKSANAAN NATIONAL SINGLE WINDOW DENGAN PEMBERLAKUAN HARMONIZED SYSTEM BERDASARKAN PERATURAN MENTERI KEUANGAN - Intan Permata Sari Palayukan; Tjip Ismail (Jurnal Education and Development, 2023)
Indonesian Customs as a player in trade facilitation and the development of the National Single Window. Harmonized System Code is needed as a standard for naming and numbering systems used to classify trade products and their derivatives in international trade. It is now regulated by Minister of Finance Regulation No. 26/PMK.010/22 concerning Stipulation of Goods Classification System and Imposition of Import Duty Tariff on Imported Goods. It is necessary to discuss further regarding the implementation of Harmonized System with the Regulation of the Minister of Finance as it is important to determine the tariffs for import and export duties on grouped goods based on a classification system. By using a normative juridical research method to examine the written legal norms of a statutory regulation. After the ratification of the Harmonized System convention, it should be regulated in laws and regulations, as the Regulation of the Minister of Finance is not included in the types and hierarchy of laws and regulations. Likewise, Indonesia as a member of the WCO in order to support the harmonization and simplification of international customs systems and procedures, Harmonized System should be regulated in laws and regulations.